Rain Sound Design at ISI Padangpanjang as an Environmental Sound-Based Multimedia Music Work - Raihan Jamil; Emridawati Emridawati; Ibnu Sina; Nursyirwan Nursyirwan; Ade Syahputra (Musica: Journal of Music, 2026)
Rain Sound Design at ISI Padangpanjang as an Environmental Sound-Based Multimedia Music Work is a multimedia music work inspired by the sonic phenomenon of rain within the campus environment of ISI Padangpanjang. This work aims to explore the potential of environmental sound as musical material through the approaches of musique concrÃ¨te and sound design. The creative process was carried out through three main stages: exploration, experimentation, and realization. Sound materials were collected through direct field recording at several locations on campus, including the TV and Film Building, the Wind Instrument Room of the Music Department, the Performance Hall, tree-covered areas, and the water drainage area near the Nusantara Building. The recorded sound samples were then processed using Ableton Live through several techniques, including reverb, delay, equalization, looping, splicing, panning, and compression. The result of this creative process shows that the sound of rain can be developed into a musical structure consisting of three main atmospheres: before the rain, during the rain, and after the rain. This work demonstrates that environmental sound does not merely function as auditory documentation, but can also be transformed into aesthetic material in the creation of multimedia music..